PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN INDRAGIRI HULU - Khaliq, Ilham (Jurnal Tepak Manajemen Bisnis, 2015)
This research aims to identify and analyze the influence of Organizational Culture, Work Discipline and Leadership towards employees Performance In Indragiri Hulu District Secretariat, both parisially and silmultantly.This research took a sample of 138 employees of the Regional Secretariat of Indragiri Hulu. The analysis method used is multiple linear regression model and analyzed by using statistical tests SPPS program version 17.00. whereas for the hypothesis test, the researcher used the F statistical test, test of determination (R2), t test and test of correlation (r2). Method of data collection used is questionnaires with ordinal preliminary data that has been converted into a range by using the method of successive intervals (MSI).The coefficient determination developed by R2 is the relationship proportion between Y to X which is obtained that the R Squere is 0,139, or 14%. Organizational culture, discipline, and leadership while the remaining 86% is influenced by other variables which are not included in this research model. Based on the results of this research, it can be seen that there is influence between organizational culture and work discipline and leadership silmultanly and significantly. While partially organizational culture, and work discipline influence significantly to the Regional Secretariat Employee Performance in Indragiri Hulu, whereas there is no significant effect of the leadership on employee performance of Indragiri Hulu District Secretariat. Variable of organizational culture is the dominant variable affecting the performance.Keywords: Organizational Culture, Discipline, Leadership, and Performance